Here's what you do when you can't find your shoe : (ingenious inventions for pesky problems) - Perry, Andrea; Snow, Alan (New York : Atheneum Books for Young Readers, 2003)
Short poems describe crazy inventions, like footsie floss, an upside-down lens for bats, and a super spider spotter for Miss Muffet.
Young Hoosier Book Award 2005-2006.
1 3 6 7 12 13 18 19 21 25 29 33 34
Keywords: Inventions -- Juvenile poetry; Children's poetry, American; Inventions -- Poetry; American poetry; Young Hoosier Book Award Nominee 2005 -2006.